The discovery of multiple rock gongs in Nigeria - Fagg, Bernard (International Library of African Music, 1956)
The first recorded discovery of ringing rocks used for the production of musical notes was made at Birnin Kudu in Kano Emirate (9'30"E., 11 'N.) in June, 1955, during field investigations of the recently discovered rock paintings, the first to be found in Nigeria. The term ‘rock gong’ is here used to denote the small percentage of the numerous natural rock boulders, slabs, spalls and exfoliations abounding in the rocky hills of Nigeria which vibrate with a ringing tone when struck and which also show indisputable evidence of having been used as percussion instruments.
Keywords: Ethnomusicology; Percussion instruments; Lithophone; Musical instruments; Rock Gong (Instrument); Nigeria; African Music